Impact of Low-Energy and High-Energy Early Enteral Nutrition Strategies on Patient Outcomes in Acute Kidney Injury - Hou A; Zhao C (International Journal of General Medicine)
Ajuan Hou, Caiping Zhao Department of Nephrology, Xianyang Central Hospital, Xianyang, 712000, People’s Republic of ChinaCorrespondence: Caiping Zhao, Email hhjjss33@163.comObjective: To investigate the impact of different early enteral nutrition (EEN) strategies on nutritional indicators and immune function in patients with acute kidney injury (AKI) undergoing continuous renal replacement therapy (CRRT).Methods: A retrospective analysis was conducted on 60 CRRT-treated AKI patients from January 2020 to March 2024, divided into a control group (high-energy EEN) and an observation group (low-energy EEN). Nutritional indicators (albumin, prealbumin, hemoglobin), immune function indicators (CD4+, CD8+, immunoglobulin A, G, M), and clinical outcomes (ICU stay duration, CRRT duration, gastric retention) were compared.Results: Before treatment, there were no significant differences in nutritional indicators between the two groups (P > 0.05). After 7 days of treatment, the observation group showed significantly greater improvements in all nutritional indicators (P < 0.05). Immune function indicators also improved significantly in the observation group (P < 0.05). Additionally, the observation group had significantly shorter ICU and CRRT durations compared to the control group (P < 0.05).Conclusion: Compared to high-energy EEN guidance, low-energy EEN guidance significantly improves nutritional status and enhances immune function in CRRT-treated AKI patients.Keywords: acute renal failure, early enteral nutrition, EEN, nutritional indicators, immune function